Numerical study on the influence of the initiation point position on the fragmentation effect of a high-explosive rocket warhead - Bogdanov, Jovica Đ.; Marinković, Mihailo M.; Jovanović, Branislav M.; Bajić, Zoran J. (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: Rockets with high-explosive (HE) warheads are the most numerous type used for multiple launch rocket systems (MLRS). They are used for a wide range of combat tasks. Besides other design characteristics, the effect on the target depends on the position where detonation is initiated in their explosive charge. The study analyses the fragmentation effects of steel balls from the 128 mm M77 HE warhead with the standard point-detonating (PD) fuze and with a differently positioned detonating assembly.Methods: The study uses a simple numerical model for the assessment of the fragmentation effect, which requires modest resources. A numerical model of the fragmentation effect was used with Gurney’s model of explosive propulsion and Taylor’s and Shapiro’s method for the direction of the fragment velocity vector. The penetration ability of projected steel balls through hard homogenous steel was analysed using the Project Thor analytical model of kinetic energy projectile penetration.Results: The results indicate that a change in the position of the initiation point can improve the fragmentation effect of steel balls. The most significant improvement is increased fragment dispersion, causing much larger fragment impact zones. A modest increase in the fragment velocity is observed as well, mainly because the direction of the fragment velocity vector is changed. Also, the penetration ability of both types of steel balls at distances up to 50 m is sufficient for the anti-personnel role, while larger steel balls have anti-material capabilities as well. Conclusion: Changing the fuze on high-explosive warheads in order to change the position of the initiation point can be used to improve the fragmentation effect.
Keywords: warhead; detonation; fragmentation; explosive propulsion